KAJIAN PENILAIAN SENSORI SOSIS BERBASIS JAMUR MERANG (Volvariella volvaceae) DAN TEMPE - Londut Donny Pranata; Usman ' Pato; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sausage is one of the processed meat product that are quite popular in Indonesian people. The purpose of this study was to obtain the best formula of sausage  using mushroom (Volvariella volvaceae) and tempeh that meet the standard quality of sausage. This research used Complatedly Randomized Design (CRD) with four treatments and four replications. The treatments were TSB1 (ratio mushroom 80, tempeh 20), TSB2 (ratio mushroom 70, tempeh 30), TSB3 (ratio mushroom 60, tempeh 40) and TSB4 (ratio mushroom 50, tempeh 50). Data obtained were analyzed using Analysis of Variance followed by Duncan’s New Multiple Range Test (DNMRT) the level of 5%. The best treatment was a sausage of treatment TSB4 with sensory acceptance by panelist.   Keywords: sausage, mushroom, tempeh, formula